Developing skills for employability with German Partners : 8 success stories from India - Niediek, Silvia [Sonstige] (Bundesinstitut für Berufsbildung, 2011)
"This brochure presents eight success stories of skill development realised in a joint effort by Indian and German partners. German training services range from consulting services and standard education courses to tailor-made in-house training sessions. With its wide range of training offers and strong emphasis on employability, 'Training - Made in Germany' has the potential to succesfully support and promote the ongoing transformation process of the Indian training system." (Text extract, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.3.4 Asien; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Indien